Jakarta Toba Batak Subject Position in Toba Batak Mangongkal Holi Discourse: Laclau Discourse Analysis - Suzen Tobing; Agus Aris Munandar; Lily Tjahjandari; Tommy Christomy (Mudra Jurnal Seni Budaya, 2023)
A secondary burial practice known as Mangongkal Holi originated in the Toba Batak people. For hundreds of years, the Toba Batak tribe has incorporated this ceremony completely. Mangongkal Holi, unlike other Indonesian burial customs that have been successful in attracting tourists like the Ngaben and Rambu Solo celebrations, is going through an existential crisis, as evidenced by the somewhat less intense manner in which it is currently being practiced. The purpose of this study is to examine how the discourse around the Mangongkal Holi rite contributes to the development of Toba Batak cultural identity. In-depth interviews with Toba Batak tribal members served as the source of the research's data, along with a literature review. This study uses Ernesto Laclau's insight analysis as its analytical framework. According to the findings, the Mangongkal Holi ritual was articulated into four nodal points: reverence for ancestors, indifference to other religions, prestige, and unity. Based on the subject position analysis, the individuals from Jakarta Toba Batak demonstrate that there is a contingency of identity for Jakarta Toba Batak in the Mangongkal Holi discourse brought on by the individual's involvement with traditional institutions. The Mangongkal Holi rite seeks to promote clan harmony among those Jakarta Toba Batak people who have a close relationship with adat. It is no longer relevant to the social reality of Jakarta, which stresses efficiency in all aspects of life, such as time and money efficiency, for Jakarta Toba Batak people who are far from the Mangongkal Holi ceremony.